Climate change adaptation and disaster risk reduction an Asian perspectives - Shaw, Rajib; Pulhin, Juan M.; Pereira, Joy Jacqueline (Community, environment and disaster risk management ;, 2010)
Climate Change Adaptation (CCA) and Disaster Risk Reduction (DRR) are closely associated. After the Bali Conference of Parties (COP) 2007, there has been significant awareness in global and national level to make collective focus on CCA and DRR. There exists some literature on CCA, however, the linkages with the DRR is not clear. The Nairobi Work Program (NWP), facilitated by the UNFCCC (UN Framework of Convention on Climate change) and the Parties have found specific scope of actions to enhance the CCA and DRR agenda in developing countries. Different national and international agencies have started undertaking initiatives on this aspect but very few concrete measures have been implemented. At this onset, the book provides 19 case studies from 13 countries and regions in Asia. The case studies highlight different aspects of CCA-DRR entry points, like policy interventions, drought risk management, coastal management, agro-forestry, lagoon management, livelihood issues and risk communication. This book is a complimentary volume of Volume 4: Climate Change Adaptation and Disaster Risk Reduction: Issues and Challenges, which focuses on the theory of CCA and DRR and its enabling environment, CCA-DRR linkages framework of governance, education and technology, different entry points like urban, coast, forest, river, and housing; and finally provided a regional perspective of developing countries. The primary targets of this book are the students and researchers in the field of disaster risk reduction, climate change, environmental studies and related risks. The book will help them to have a better idea on the current trend of research in the field, and will provide basic knowledge on this important topic. The other target group is practitioners and policy makers for applying the collective knowledge into policy and decision making.